DESAIN BAHAN AJAR MATEMATIKA SMA/SMK BERBASIS HOTS - Eris Fanny Firdaus; Eka Farida Fasha; M. Faisal Abduh (Department of Mathematics Education, Universitas Kuningan, 2021)
This research is a development research with the aim of this research is to obtain HOTS-based mathematics textbooks that are valid and suitable for use and can support students' mathematical abilities, one of which is high-order thinking skills. The 2013 curriculum emphasizes modern pedagogical dimensions in learning, namely using a scientific approach. The research method used is development research or known as RD (research and development). R D model used is Borg and Gall which includes the following stages: preliminary study, design, product development. The final stage of Borg and Gall's RD research method is implementation. Researchers used the modified results of the Borg and Gall RD research method due to limited research time and ineffective pandemic conditions for maximum implementation, as evidenced in a limited trial of online learning to one class XI SMA only about 20% responded. The teaching materials developed are in the form of learning modules for SMA and SMK levels. The results of this study can be concluded that the developed book products meet the very good criteria of each category. In other words, the developed book product is said to be valid and suitable for use.